Case Report: Virtual and Interactive 3D Vascular Reconstruction Before Planned Pancreatic Head Resection and Complex Vascular Anatomy: A Bench-To-Bedside Transfer of New Visualization Techniques in Pancreatic Surgery - Templin, Robert; Tabriz, Navid; Hoffmann, Martin; Uslar, Verena Nicole; Lück, Thomas; Schenk, Andrea; Malaka, Rainer; Zachmann, Gabriel; Kluge, Alexander; Weyhe, Dirk (Frontiers in Surgery, 2020)
Introduction: Bühler's anastomosis (or Bühler’s arcade) is an embryonic relic and represents an arterio-arterial connection between the superior mesenteric artery and the celiac trunk. It can be found as a variety in 1-2% of patients. Case Presentation: We present a case of a patient with metatastatic squamous cell carcinoma of the lung. The patient was in stable disease for 4 years under palliative therapy (most recently second-line therapy with Nevolumab). In 2019, a locally advanced adenocarcinoma of the papilla vateri was diagnosed, additionally. The patient also underwent right hemicolectomy and patch plasty of the celiac trunk and superior mesenteric artery due to colonic ischemia and arteriosclerotic disease with 50-70% stenosis of the superior mesenteric artery several years ago. Due to a complex vascular prehistory, the standardized preoperative imaging was supplemented by two independent vascular reconstructions (a CT angiogram and a reconstruction based on the CT) for the planning of a pylorus-preserving pancreatic head resection and reconstruction according to Traverso-Longmire. In addition, a 3D print was produced. Both, the reconstruction based on the CT scan and the 3D print were created for off-label use as a part of a research project (VIVATOP: Versatile Immersive Virtual and Augmented Tangible OP). Discussion: In the standardized CT scan and in the clinical CT-angiography, there were no obvious surgically relevant anatomical variations. A Bühler anastomosis was detected in a digital, virtual and interactive 3D-reconstruction. In addition, in the 3D print of the abdominal site the anastomosis was seen as well. Intraoperatively, the presence of Bühler's anastomosis was confirmed. This information had a significant impact on the intraoperative approach. Retrospectively, the vessel variant could be surmised in the axial projection of the CT scan, if one knew what to look for. Conclusion: For the conduction of a safe surgical procedure, it is imperative that rare anatomical variations are known preoperatively. Increasing digitalization in surgical and perioperative preparation holds great potential for better planning and improved patient safety. Research and cooperation projects such as the VIVATOP project are instrumental for the development of new visualization techniques, which are able to enhance the understanding of complex anatomical relations.